A LITERATURE REVIEW OF COERCIVE ISOMORPHISM ON CORPORATE LEGAL RESPONSIBILITY IN INDONESIA - Muhamad Romdoni (PRANATA HUKUM, 2022)
This paper analyzes the effect of coercive isomorphism (legal system) in Indonesia. It is necessary to improve a kind of reform in a directed and integrated manner, both related to codification and specific legal fields, to support the development in various aspects of society. If we refer to the Law Outside the Criminal Code, there are several crucial issues, such as accountability for criminals as subjects of criminal Law. This research is a literature study as a review of corporate criminal liability by using the method juridical empirical. From a series of studies and in-depth studies conducted, the authors found several systems of corporate criminal liability, such as doctrinal Strict Liability, the doctrine of Vicarious Liability, and the doctrine of direct corporate criminal responsibility, to the teachings of the Corporate Culture Model. For example, in applying the Vicarious doctrine, liability to corporations is contained in Article 116 paragraph (2) UUPPLH. Some of the results of the studies in this study led to an evaluation and essential recommendations related to aspects of corporate criminal liability in the legal system in Indonesia.